Perbedaan Tingkat Caregiver Burden Yang Merawat Lansia Demensia Di Panti Wreda - Heru Ginanjar Triyono; Meidiana Dwidiyanti; Rita Hadi Widyastuti (Holistic Nursing and Health Science, 2018)
Background: The prediction of the number of elderly people in Indonesia will increase along with changes in Indonesia's demographic status. Elderly people who feel that at home less socialize with elderly people choose to live in a nursing home, this is an alternative for the elderly, elderly degenerative diseases are very diverse one of which is elderly dementia with dementia will require a level of dependence beyond the elderly who do not have dementia. Caregivers who treat the elderly with dementia will be very vulnerable to burden in treating elderly dementia.Purpose: The purpose of this study was to analyze the difference in the level of caregiver burden who care for elderly dementia at a nursing home.Method: This research method uses "Quasy experiment pre and posttest with control group". Number of samples 34 from each group. Data were analyzed using the Mann Whitney test with the help of SPSS 22.0 for Windows.Results: Research in the control group has a higher level of burden caregivers compared to intervention groups, this is because the control group respondents have lower wages than the city minimum wage, besides that the elderly characteristics carried out by nursing care have more severe dementia than the intervention group.Conclusion: The results of this study can be used as a reference in developing services for the elderly and elderly caregiver, especially the elderly who suffer from dementia.